Analysis of Citizen Reluctance in Legislative Service: Experience from the Indonesian Parliament - Budi Santoso, Priyo (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This study discusses SIDUMAS, a digital platform developed by the Indonesian House of Representatives (DPR-RI), to accommodate public aspirations and complaints. The goal is to strengthen communication and transparency between legislative institutions and citizens. Although this platform brings several advantages, such as faster processes and easier access, many people still have not utilized it. It shows a gap between the government’s enthusiasm in building a digital system and the public’s readiness to use it. The results revealed that low digital literacy, lack of information about SIDUMAS, and low trust in legislative institutions are the main factors that hinder public participation. Therefore, the success of this service is highly dependent on efforts to improve digital understanding, build trust, and socialize this platform comprehensively. Finally, this study contributes to how the application of technology, such as SIDUMAS, can be utilized in public services and various government institutions, more specifically, considering the community’s user preferences. This finding also underlines that digital innovation is not enough just to be available; it must be adapted to the community’s social conditions and be easily accessible to all groups.